The Differential Metabolic Profiles Between Deltamethrin-Resistant and -Susceptible Strains of Aedes albopictus (Diptera: Culicidae) by 1H-NMR. Issue 3 (25th December 2020) - Huang, Lianfen; Li, Jun; Peng, Lilan; Xie, Ruili; Su, Xinghua; He, Peiqing; Xu, Jiabao; Jia, Zhirong; Luo, Xiaoting; Chen, Xiao-Guang; Li, Hua
Abstract: Metabolomics can indicate the physiological and biochemical responses of mosquitoes to different stimulants, including insecticides, which allow them to adapt to different inhospitable environments. Though metabolic differences between insecticide-resistant and -susceptible strains have been established for other mosquito species, such as Anopheles and Culex, it is yet to be done for Aedes albopictus (Skuse). In this study, nuclear magnetic resonance (NMR) spectroscopy–based metabolomic analysis performed on Ae. albopictus deltamethrin-resistant and -susceptible strains showed significant differences in amino acid, organic acid, and sugar metabolism. Concentrations of neutral amino acids and sugars tended to be lower in the deltamethrin-resistant strain than in the deltamethrin-suceptible strain, but the concentration of basic and acidic amino acids and organic acids increased. All these changes might accommodate biochemical and physiological needs in deltamethrin-resistant mosquitoes, such as enzyme synthesis and detoxification. This was further confirmed by the predictable draft metabolic map. This is the first report using NMR spectroscopy to investigate the metabolic differences between deltamethrin-resistant and -susceptible strains of Ae. albopictu s. To a certain degree, this demonstrates how Ae. albopictus develop insecticide resistance by metabolic reprograming to survive under the insecticide pressure.